FREQUENCY OF NO-REFLOW IN PATIENTS UNDERGOING PRIMARY PERCUTANEOUS CORONARY INTERVENTION AND THE IMPACT OF INTRACORONARY ADRENALINE AND TIROFIBAN ON TIMI FLOW - Ullah, Ikram; Hamidullah,; Farooq Ahmad,; Sajjad Khan,; Hafiz Adil Bilal,; Samiurehman, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Coronary interventions, including percutaneous coronary intervention (PCI), have significantly improved management of coronary artery disease by restoration of coronary blood flow to myocardium. However, despite of so many advancements in PCI procedural techniques, there is still a significant and challenging complication known as the "no-reflow" phenomenon exists which worstly effect the PPCI outcome. Methods: It was Cross sectional study conducted at Department of Cardiology, Lady Reading Hospital Peshawar. Study was conducted from 1/1/2023 to 30/6/2023 for six months. All patients who developed no reflow were subjected to intracoronary Tirofiban. Those who do not responded to Tirofiban were given intracoronary adrenalin and effect was noted. Data were analyzed using SPSS Version 23.0. Mean and standard deviation were calculated for quantitative variables like age. Frequencies and percentages were calculated for categorical variables like gender. The p-value less than 0.05 was considered significant. Results: Among 151 participants, 18% experienced the no-reflow phenomenon. Intracoronary adrenaline and Tirofiban individually showed a significant positive impact on TIMI flow. It was found that 40% patients with no reflow responded to Tirofiban administration. Remaining patients with no reflow were subjected to intracoronary adrenalin therapy and 74% of these patients had improved TIMI flow. It was also found that combine effect of Tirofiban and adrenalin was found in 84% of patients. Conclusion: No reflow phenomenon is common finding in Primary PCI and can be effectively managed by Tirofiban and intracoronary adrenalin administration in most cases.